From Imperial Russia’s Plenipotentiary in Mongolia I. Ya. Korostovets to Representative of RSFSR People’s Commissariat of Foreign Affairs O. I. Makstenek: Celebrating the 100th Anniversary of Russia-Mongolia Diplomatic Relations - Leonid V. Kuras; Bazar D. Tsybenov (Монголоведение, 2021)
Introduction. An urgent issue of Mongolian studies today is the role of Russian-Mongolian diplomatic relations in promoting the statehood of Mongolia in the first quarter of the twentieth century. The revolutionalry movement in Inner Asia, in particular, and the social-political history of modern Mongolia, in general, are closely associated with the efforts of Russian diplomacy and, especially, with a number of diplomats who greatly contributed to the promotion of Mongolian direction of the Russian politics in the East. The aim of the present article is the study of the activities of Russian diplomats, namely I. Ya. Korostovets, the Plenipotentiary of the Imperial Russian Government in Mongolia, and O. I. Makstenek, the Representative of the People’s Commissariat of Foreign Affairs of the RSFSR in Mongolia. Accordingly, the research has been conducted along the following lines: i) history of the issue, ii) examination of 1912 Russian-Mongolian agreement, iii) description of the events in Outer Mongolia between 1917 and 1920, and iv) analysis of Makstenek’s report as a source on the history of Mongolian Revolution of 1921 and the Soviet-Chinese relations. Conclusions.Both Korostovets, on behalf of the Russian Imperial Government, and Makstenek, on behalf of the RSFSR, played a significant role in establishing the regional system of international relations in the Baikal region. The 1912 Russian-Mongolian Agreement, which was in fact the result of Korostovets’ efforts, was instrumental in promoting Mongolia as a subject of international law and in initiating the movement of Mongolians to their de facto and de jure independence from China. Makstenek’s report shows much effort the Soviet diplomat took in preparing the Mongolian Revolution of 1921. Besides receiving and delegating Mongolian revolutionaries to Soviet Russia, taking an active part in preparations to the First Congress of the Mongolian People’s Revolutionary Party and in the formation of military detachments of Mongolian People’s Revolutionary Army, Makstenek conducted negotiations with the Chinese authorities in Urga and Maimachen, i.e. in fact initiated the diplomatic proceedings designed to prepare the presence of Soviet troops in Mongolia.